Karakteristik Produk Tradisional Ikan Tongkol Asap dari Kabupaten Natuna, Kabupaten Bintan dan Kota Tanjungpinang, Provinsi Kepulauan Riau - Ismael Marasabessy; Raja Marwita Sari Putri; Lily Viruly; Yulia Oktavia; Ginanjar Pratama; Aidil Fadli Ilhamdy; Ersti Yulika Sari; Jumsurizal Jumsurizal; Tetty Tetty (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2022)
One of the typical traditional products from the Riau Islands is “ikan tongkol asap”. These products are spread in several cities and regencies in the Riau Islands Province. Some areas that are famous for producing “ikan tongkol asap” traditionally are Natuna Regency, Bintan Regency and Tanjungpinang City. This study aims to determine the characteristics of “ikan tongkol asap” products based on the type of fish used, chemical composition, and organoleptic assessment. The research was conducted descriptively by taking samples of “ikan tongkol asap” products from several entrepreneurs on Bintan Island (Bintan and Tanjungpinang) and Bunguran Island (Natuna). The research stages were carried out by identifying the fish raw materials used for “ikan tongkol asap” products, morphometric analysis, organoleptic/sensory analysis, and proximate analysis of the product. In this study, it was found that the raw materials used for smoked fish were Thunnus tonggol, Auxis thazard, Euthynnus affinis, and Katsuwonus pelamis. Morphometrically, the fish used were 43.50-46.25 cm in length, and 1.25-1.85 kg in weight. In the sensory analysis with the parameters of appearance, aroma, taste, and texture, the overall products from the three regions were not significantly different. Based on the proximate analysis, each smoked fish product has its own value from each region with crude protein values ​​ranging from 34.04-45.28%. The sensory and proximate are in accordance with the SNI 2723:2013, except for the moisture content of